Assessment of microalgae cell culture growth regulatory mechanism towards different medium formulation, light intensity and photoperiod - Othman, Rashidi; Shaharuddin, Ruhul Izzati; Wan Sulaiman, Wan Syibrah Hanisah (2017)
The cell culture growth regulatory mechanism for microalgae is depending on various factors such as medium composition, light intensity and photoperiod. Significantly, it will influence economical important through productivity of large scale microalgae for commercialization in order to achieve the maximum growth. In the present study, effects of different culture medium, light intensity and photoperiod were investigated through batch culture of two groups of algae which are cyanobacteria (blue green algae) and green algae. The blue green algae species that consist of Pseudanabanae sp. and Synechochoccus sp. while the green algae consist of Pandorina morum and Chlorella vulgaris were tested in four different medium (Chu 10, Bg11, Bristol’s and Bold’s Basal Medium) with five photoperiod cycle (Light: Dark) , 0:24, 12:12, 18:6, 16:8, and 24:0. The results revealed that all species with high optimal growth in the BG-11 medium under a light intensity of 60 lmol m-2 s-1 and 12:12 (Light: Dark) cycle. However, cyanobacteria well grew in the dark. Colour changes are valued with CIELAB Reflectance Colorimeter. The colour pigmentation changed from green to yellowish was observed in Chu 10. The cell of algae pigmentation is normal in BG 11. Thus, optimization of growth rate for microalgae has a different value according to species and factors influences.